Freshwater nematodes : ecology and taxonomy (CABI, 2006)
This book contains 22 chapters on various aspects of freshwater nematode ecology and taxonomy. Subjects covered include the techniques for processing freshwater nematodes, the composition and distribution of free living freshwater nematodes, their abundance, biomass and diversity, the production of freshwater nematodes, their feeding ecology, patterns in size structure of freshwater nematode communities, different nematode habitats, and computation and application of nematode community indices. It provides descriptions with figures of each taxon at the genus level and above to currently valid genera. For every genus, a complete list of species, with an emphasis on biogeography, is given for primarily freshwater taxa and a list of only those species reported from freshwater bodies is given for the genera that are considered primarily non-freshwater. This book is intended to provide a useful reference to students, beginners and established researchers in the field of freshwater nematology, benthologists, invertebrate biologists, limnologists, ecologists, microbiologists and soil biologists.